The phratries of Attica - Lambert, S. D. (Univ. of Michigan Pr., 1993)
The Phratries of Attica provides the first comprehensive account in English of a key institution in ancient Athens: the Attic phratries. These hereditary groups of citizens, linked to one locale or more in Attica, played a crucial role in regulating access to Athenian citizenship. The author concentrates upon the evidence - largely empirical - for the period 450-250 B.C., but he also considers the role of the phratry in the reforms of Cleisthenes and examines the institution's probable demise in the second century B.C. S. D. Lambert adopts an innovative view in his argument that phratries reflected the democratic norm of the era, rather than being dominated by aristocrats. In presenting this view he includes a complete account of the festival Apatouria, of the procedures for admission to citizenship, of the role of women in phratries, and of known phratry property and financial transactions. The Phratries of Attica will be indispensable to students of Greek and Athenian history and anthropology. An Appendix contains all inscriptions connected to Attic phratries, with translation and selective commentary.
Keywords: Alltag, Brauchtum; Citoyenneté - Grèce - Athènes; Clans - Grèce - Athènes; Fratrieën; Parenté - Grèce - Athènes; Citizenship -- Greece -- Athens; Clans -- Greece -- Athens; Kinship -- Greece -- Athens; Phratrie; Athènes (Grèce) - Murs et coutumes; Athènes (Grèce) - Vie religieuse; Griechenland; Athens (Greece) -- Religious life and customs; Athens (Greece) -- Social life and customs; Attika